2010
DOI: 10.1021/ac102002k
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Voltammetric Detection Using Individually Addressable Oligonucleotide Microelectrode Arrays

Abstract: The utility and performance of label-free, oligonucleotide probes for reagentless detection of dilute target analytes was examined using a voltammetric transduction principle in an array format. Multistep, solid-state fabrication yielded preproduction arrays of 16 individually addressable, 30 μm diameter microelectrodes in a 30 mm × 6.5 mm × 0.5 mm dipstick disposable device. The specificity of 16 nucleotide (nt) 2'-O-methylribonucleic acid and 22 nt DNA backbone probes bound through Mg(2+)-phosphonate bridges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
2
22
0
1
Order By: Relevance
“…8a) decreased while the peak of P/G 1:100 sensor (inset of Fig. Kalantari et al reported that the target length (38, 107, 1788 and 2907 base pairs) can contribute to changes in the hybridization signal, 46 which was in good agreement with the P/G sensor. In Fig.…”
Section: Real Sample Analysissupporting
confidence: 62%
“…8a) decreased while the peak of P/G 1:100 sensor (inset of Fig. Kalantari et al reported that the target length (38, 107, 1788 and 2907 base pairs) can contribute to changes in the hybridization signal, 46 which was in good agreement with the P/G sensor. In Fig.…”
Section: Real Sample Analysissupporting
confidence: 62%
“…All experiments were conducted using a chip consisting of an array of 16 platinum microdisk electrodes, soldered to the printed circuit board and connected to 16 channel multipotentiostat .…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for assembly of MEA with polypyrrole bilayer were already reported . Briefly, the polypyrrole bilayer was chronocoulometrically deposited in a two‐step procedure using 0.1 M pyrrole and then 0.1 M poly[2,5‐dithienyl‐(N‐3‐phosphorylpropyl)pyrrole] (TPT−C3−PO 3 H 2 ), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microelectrode arrays (MEAs) constitute a widely used platform that enables spatially highly resolved parallel sensing [ 1 , 2 , 3 , 4 , 5 , 6 ]. Owing to the advances in microfabrication technology, established methods for manufacturing microelectrodes from a large variety of materials over a wide range of geometries and spatial arrangements are available [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%